(untitled) (Eurasian Journal of Research, Development and Innovation, 2025)
This article explores how inclusive education principles can be effectively implemented in EFL teaching to support students with diverse learning needs, including those with disabilities. Drawing on international definitions and perspectives, as well as recent empirical studies, the paper examines the challenges teachers face in inclusive EFL settings and analyzes research-based strategies that promote accessibility and equity in language learning. Key findings emphasize the effectiveness of differentiated instruction, the integration of assistive and educational technologies, task-based learning, multimodal strategies, and the critical role of teacher attitudes and professional development. The study concludes that inclusivity in EFL education is both a pedagogical and ethical imperative, requiring systemic support and ongoing innovation.